SKETSA PENELITIAN KUALITATIF DALAM PENDIDIKAN - Moh. Zamili (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2013)
What will I do before researching? Why is there a formulation of the problem or research question? What is the data and how the data words to be? How I would process the data that has been collected? How to analyze the data so that it becomes valid research reports? Such questions, hopefully, may be answered in the study conceptual and theoretical analysis on this paper, especially we who use qualitative models. Moreover, the results of this analysis have stressing on education where development and the context of the current literacy research will be alienated if educational researchers tend to use quantitative research models. Because the phenomenon and the reality of education are too unique to be quantified, even the complexity of education is too sublime to percentage.